An application for nonlinear control by input-output linearization technique for pm synchronous motor drive for electric vehicles - Boucha Abdellah; Hazzab Abdeldjebar; Khessam Medjdoub (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper leads to present the modified approach of the speed control for permanent magnet synchronous motors applied to electric vehicles using a nonlinear control. The motor's nonlinear dynamics are transformed into a linearized system model using the input-output feedback linearization technique. There are two permanent magnet synchronous motors (PMSM) in the propulsion model. In order to improve the motor's output torque, the direct component of the current is adjusted to zero. The electronic differential, which is used in the calculations, enables each driving wheel to be controlled individually at each curve. The MATLAB/Simulink software is used to implement modeling and simulation in order to assess the effectiveness of the suggested solution. Simulation studies are used to confirm the efficacy of the proposed technique. The obtained results signify that this approach is more accurate.